Emotional nursing by syndrome differentiation combined with narrative nursing for a patient with blood stasis and qi stagnation type lumbar disc herniation accompanied by emotional distress (中医辨证施志联合叙事护理调节腰椎间盘突出症患者情志不畅的护理体会) - CHU Yina (初伊娜); ZHANG Yunxia (张云霞); TIAN Jing (田婧); ZHANG Xiaoya (张晓雅); HU Yaxin (胡雅鑫); CHEN Rui (陈蕊); LUAN Huadi (栾华迪); ZHANG Linyan (张林燕); GAO Xinxia (高新霞) (Journal of International Translational Medicine Limited, 2024)
This paper summarized the practice of emotional nursing by syndrome differentiation combined with narrative nursing for a patient with blood stasis and qi stagnation type lumbar disc herniation accompanied by emotional distress. Based on the analysis of Traditional Chinese Medicine pathogenesis of lumbar disc herniation and concept of emotional nursing by syndrome differentiation, the technique of clearing tendons and moving cupping along the bladder meridian on the back, the six character formula breathing method, dietary regulation, and daily life maintenance were carried out to relieve the emotional distress symptoms. Individualized nursing interventions by using narrative nursing skills were carried out to relieve the negative emotions of the patient. (本文总结1例采用中医辨证施志联合叙事护理方法调解腰椎间盘突出症患者情志不畅的护理经验。基于腰椎间盘突出症中医病机以及中医辨证施志理论, 给予背部足太阳膀胱经循筋解结走罐技术、六字诀吐纳法、饮食调护、日常生活养护等护理措施调节患者情志不畅的护理问题, 并运用叙事护理的沟通技巧, 为患者情志不畅症状提供了个性化护理, 有效缓解了患者的负性情绪。)